1990
DOI: 10.1007/bf02602307
|View full text |Cite
|
Sign up to set email alerts
|

Teaching humanistic and psychosocial aspects of care

Abstract: Most of the training that does occur in the humanistic/psychosocial aspects of care probably happens informally via mentoring and role modeling. Appeals to expand teaching in these areas raise questions regarding what to include in medical training and the proper scope of internal medicine. Sustainable change will depend on the politics of resource distribution and the influence of general internal medicine and primary care on traditional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The 47-item questionnaire was designed based on a literature review and previous surveys (Merkel et al 1990;Rosenzweig 1991;Novack et al 1993), and survey items were reviewed by a group of experts for face validity. Representative questionnaire items and characteristics of the questionnaire are presented in Table 1.…”
Section: Questionnairementioning
confidence: 99%
“…The 47-item questionnaire was designed based on a literature review and previous surveys (Merkel et al 1990;Rosenzweig 1991;Novack et al 1993), and survey items were reviewed by a group of experts for face validity. Representative questionnaire items and characteristics of the questionnaire are presented in Table 1.…”
Section: Questionnairementioning
confidence: 99%
“…Indeed, many medical schools still attend poorly to training in interviewing (Novack et al, 1993), many interviewing texts neither reference «patient-centered« nor evince its practice in their recommendations, and many residencies don't effectively broach the topic (Merkel et al, 1990;Parrino & Kern, 1994;Sullivan et al, 1996) -all of which encourage and reinforce an isolated doctor-centered interviewing approach. And all this in light of the well documented benefits from integrating patientcentered and doctor-centered interviewing methods.…”
Section: Patient-centered Interviewing Can Transform Mainstream Medicmentioning
confidence: 99%
“…Instruction in patient education, however, is up against stiff competition for curriculum time. A survey of internal medicine residency programs accredited in 1985-1986 found that only 44% of 434 responding residency program directors reported that their programs offered mandatory training, and only 18% of the programs offered elective training, in patient education-related areas (19). Obstacles cited by residency directors included insufficient curriculum time (51%), lack of trained faculty (44%), and pressures to reduce both training costs (40%) and patient care costs (37%).…”
Section: Training In Patient Education For Physiciansmentioning
confidence: 99%